Noninvasive Ventilation in Patients With COVID-19-Related Acute Hypoxemic Respiratory Failure: A Retrospective Cohort Study - Fu, Yingyun; Guan, Lili; Wu, Weibo; Yuan, Jing; Zha, Shanshan; Wen, Junmin; Lin, Zhenghao; Qiu, Chen; Chen, Rongchang; Liu, Lei (Frontiers in Medicine, 2021)
Introduction: Noninvasive ventilation (NIV) has been used to alleviate hypoxemia and dyspnea, but there is no consensus on the application of NIV in patients with coronavirus disease 2019 (COVID-19). Some staff use NIV as the rescue therapy which might lead to the adverse outcomes. This study was to identify early factors associated with intubation to help the medical staff select appropriate patients for receiving NIV treatment. Methods: Patients with laboratory-confirmed COVID-19 who were treated with NIV in emergency department or ICU of the Third People’s Hospital (the only designated hospital for treating COVID-19 in Shenzhen) between January 1 and August 31, 2020, were retrospectively analyzed. Results: 39 patients with COVID-19 treated with NIV were included; of them, 16 (41%) received endotracheal intubation and 3 (8%) died. Significant differences were observed between intubated and nonintubated patients in PaO2/FiO2 before NIV initiation, hospitalization duration, NIV as the rescue therapy, and PaO2/FiO2 of ≤200mmHg after 1–2h of NIV initiation. Notably, 1–2 h after NIV initiation, a PaO2/FiO2 of ≤200mmHg (odds ratio [OR], 9.35; 95% confidence interval [CI], 1.84–47.62; P=0.007) and NIV as the rescue therapy (OR, 5.43; 95% CI, 1.09–27.12; P = 0.039) were the risk factors for intubation. Conclusions: In patients with COVID-19-related acute hypoxemic respiratory failure receiving NIV, close attention should be paid to PaO2/FiO2 after 1-2h of NIV initiation. Also, using NIV as rescue therapy should draw our awareness that it might delay escalation of respiratory support and lead to adverse outcomes.